Boy with chemistry set at Christmas (1937)
General view of an unidentified man and young boy posed in front of a Christmas tree in a domestic setting. A chemistry set, presumably a gift, is visible in front of the boy.
Keywords: Chemistry sets; Educational toys; Christmas; Children